IMPLIKASI HUKUM INTERNASIONAL PADA FLIGHT INFORMATION REGION (FIR) SINGAPURA ATAS WILAYAH UDARA INDONESIA TERHADAP KEDAULATAN NEGARA KESATUAN REPUBLIK INDONESIA - Eco Silalahi; Maryati Bachtiar; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The sovereignty of a country is the highest power state of that country how to govern and enforce the law in the territory. As one of the largest country in the world, Indonesia was not sovereign over the territory, in particular airspace. The airspace of Riau Islands and Natuna until 1946 is controlled by Flight Information Region (FIR) Singapore. It means that every flight in that airspace must received permission from Singapore, including Indonesia itself. Indonesia is supposed to be ruling all of Indonesia territory without delegating to any party.According to above description, The author is interested to doing research with the title Implication of the International law in Flight Information Region Upper the Airspace of Indonesia Againts Sovereignty of the Republic of Indonesia. This thesis aims to determine how the navigation settings in Indonesia. Furthermore, to determine the implications of the delegation the airspace of Riau Islands and Natuna to Singapore FIR against Indonesian sovereignty.In the thesis, the author uses the method of normative legal research. Data sources supported by the data source of primary, secondary and tertiary. While data collection techniques is the study of literature and study data using deductive method is to analyze the problems of a general nature and then drawn to a conclusion in particular based on existing theory.The results of the discussions in this thesis is, first, Flight navigation settings in Indonesian airspace divided into three, namely, Jakarta FIR which covers the western part of the Borneo island to the western part of Indonesia began western part of Central Java and Christmas Island belongs to Australia. Ujung Pandang FIR covers the eastern part of Indonesia, ranging from the eastern part of the island of Borneo, and East Java up to Papua, plus one FIR Singapore covering airspace Riau and Natuna Islands, which is divided into three sectors, namely A, B and C. Second, the implications of the delegation of airspace and Natuna the Riau Islands to Singapore FIR against Indonesia is divided into three, namely, the first in the fields of politics will affect the position of Indonesia in the civil aviation of world that have an impact on the public's view of the ability of Indonesia, especially in the flight will be low-cost. In economics, income from fee of airspace across Riau Islands and Natuna is not achieved by Indonesia as full as must be, because Singapore collects the fee does not provide the transparency of the number of flights across the region. Finally, in the field of defense and security, Indonesia must be vigilant because the area is also used by Singapore to conduct military exercises. So can damage parts of Indonesia and Indonesian security defense harm.Keywords: Implications, delegation, airspace, FIR Singapore